Association of baseline cytokines with antibody concentrations after diphtheria-tetanus-acellular pertussis booster vaccination in Finnish children - Anabe, Denise; Teräsjärvi, Johanna T.; Barkoff, Alex-Mikael; Knuutila, Aapo; Pape, Bernd; van Gageldonk, Pieter; Buisman, Annemarie; Mertsola, Jussi; He, Qiushui (Vaccine, 2025)
Despite extensive vaccinations, pertussis remains endemic and epidemic in multiple countries. The persistence of cases can be partly attributed to the significant individual variation in vaccine responses. This study evaluated the association of baseline cytokines (before booster vaccination) on antibody concentrations to Tdap-vaccine antigens. Healthy Finnish children (7–10y, n = 36), adolescents (11–15y, n = 37), young adults (20–34y, n = 25), and older adults (60–70y, n = 23) received a Tdap3-IPV booster. Serum antibodies against pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin (Prn), fimbriae 2/3, diphtheria toxoid (DT), and tetanus toxoid (TT), as well as PT neutralizing antibodies were measured before, one month, and one year after the booster. Baseline serum concentrations of IFN-γ, IL-2, IL-5, IL-10, IL-13, IL-17 A and IL-17F were determined. The proportion of detectable and undetectable baseline cytokines varied between age groups 58.3 % of children had a higher proportion of detectable IL-5, IL-10, IL-13, and IL-17F compared to adolescents (IL-5, 37.8 %; IL-10, 48.6 %; IL-13, 48.6 %; IL-17F, 37.7 %), young adults (IL-5, 36.0 %; IL-10, 28.0 %; IL-13, 36.0 %; IL-17F, 44.0 %), and older adults (IL-5, 26.1 %; IL-10, 21.7 %; IL-13, 39.1 %; IL-17F, 30.4 %). IFN-γ had a lower detectability in children (44.4 %) and young (40.0 %) and older adults (39.1 %) in contrast to adolescents (62.2 %). IL-2 was undetectable in all age groups while the proportion of detectable IL-17 A decreased with age. A mixed model showed that undetectable baseline levels of IFN-γ, IL-2, IL-10, and IL-17 A were associated with higher antibody concentrations in children before and after vaccination, particularly against PT. Positive associations were observed in adolescents for anti-TT concentrations and young adults for anti-FHA IgA concentrations. These findings indicate a possible role of existing cytokines in pertussis booster antibody concentrations in children and warrant further studies in different populations. However, the results should be interpreted with caution as the number of subjects is limited. •There is significant individual variation in pertussis vaccine responses.•Baseline cytokines are associated with antibody concentrations to Tdap antigens.•Undetectable cytokines are linked to higher antibody concentrations in children.•Undetectable cytokines are linked to lower antibody concentrations in older age groups.